Competitive strategies, innovation, and firm performance: an empirical study in a developing economy environment - Bayraktar, Cahit Ali; Hancerliogullari, Gulsah; Cetinguc, Basak; Calisir, Fethi (Informa UK Limited, 2016)
ABSTRACTThis paper studies the relationships between competitive strategies, innovation, and firm performance within the context of Turkish manufacturing companies. The data were collected from top management of the firms via Computer Assistant Telephone Interviewing method. One hundred and forty manufacturing firms operating in various sectors including textile, automotive supply, computer and electronics provide the basis for this empirical research. In order to test our model, we employ structural equation modelling using partial least squares. The results show that competitive strategies such as cost-leadership and differentiation can lead to innovation, which, in turn, increase firm performance. Managers implement cost-leadership and differentiation strategies to take part in competitive market conditions; however, they should put additional importance on innovation that plays a significant role as a bridge between competitive strategies and firm performance.